Distinct Trajectories of Physical Activity Among Patients with COPD During and After Pulmonary Rehabilitation. (3rd September 2015) - Saunders, Travis J.; Dechman, Gail; Hernandez, Paul; Spence, John C.; Rhodes, Ryan E.; McGannon, Kerry; Mundle, Stephen; Ferguson, Carol; Bourbeau, Jean; Maltais, Francois; Marciniuk, Darcy D.; Camp, Pat G.; et al.
Abstract: Little is known about longitudinal trends in objectively measured physical activity (PA) during and after pulmonary rehabilitation (PR) for individuals with Chronic Obstructive Pulmonary Disease (COPD). The purpose of this study was to examine the PA trajectories of patients with COPD during and after PR and whether demographic, clinical, or program characteristics differed across these trajectories. The study was approved by Research Ethics Boards at all participating institutions, and written informed consent was obtained from each participant prior to study inclusion. COPD patients (N = 190) completed a questionnaire and wore a pedometer for 7 days at baseline, end of PR, and 3 and 9 months after completing PR. Latent class growth analyses showed that two distinct PA trajectories emerged. Active Maintainers averaged 9177 steps/day at baseline, and maintained this level throughout the assessment and post rehabilitation period. In contrast, Inactive Maintainers averaged 3133 steps/day at baseline, which also remained stable during and after PR. Follow-up analyses showed the Inactive Maintainers were more likely to be retired from work and have lower baseline scores for their stress tests and 6-minute walk tests compared to Active Maintainers (all p < 0.05). These results suggest that two distinct steps/day trajectories exist for COPD patients during and after completing PR that are partially explained by specific demographic and clinical characteristics.